2018
DOI: 10.1371/journal.pone.0202110
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol-induced hepato- and nephrotoxicity in rats: Role of Curcumin and Gallic acid as antioxidants

Abstract: Tramadol is an analgesic used to treat moderate to severe pain caused by cancer, osteoarthritis, and other musculoskeletal diseases. Cytochrome P450 system metabolizes tramadol and induces oxidative stress in different organs. Therefore, the present study aims at investigating the changes in the activities and the protein expressions of CYPs isozymes (2E1, 3A4, 2B1/2), antioxidants status, free radicals levels after pretreatment of rats with Curcumin and/or Gallic as single- and/or repeated-doses before admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 67 publications
(63 reference statements)
9
23
0
Order By: Relevance
“…Tra doses of 50 and 75 mg/kg signifi cantly decreased the intracellular GSH content, compared to the control group. In agreement with our study, Ghoneim et al (12) and Sheweita et al (46) reported that Tra exposure decreased the GSH storage in the testis, cortex, liver and kidney tissues. Depletion of GSH in the testis can cause severe defi ciency in the antioxidant defence system, leading to the further elevation of LPO.…”
Section: A B Csupporting
confidence: 94%
“…Tra doses of 50 and 75 mg/kg signifi cantly decreased the intracellular GSH content, compared to the control group. In agreement with our study, Ghoneim et al (12) and Sheweita et al (46) reported that Tra exposure decreased the GSH storage in the testis, cortex, liver and kidney tissues. Depletion of GSH in the testis can cause severe defi ciency in the antioxidant defence system, leading to the further elevation of LPO.…”
Section: A B Csupporting
confidence: 94%
“…The improvement occurred in the tested liver biomarkers by turmeric extract or kiwifruit juice or their combination may be attributed to their ability in preventing and repairing the cell membranes of the hepatocytes injured by tramadol administration as they have a potency of antioxidants which prevent the lipid oxidation of the liver cell membranes. These results are confirmed by Sheweita et al (2018) who found that giving curcumin prior to tramadol administration to rats alleviated the changes in the antioxidant capacity and the marker enzymes of liver and kidney because of tramadol intake. They attributed this protective effect to the ability of curcumin for scavenging of reactive oxygen species (ROS) and suppression of the oxidative stress.…”
Section: Effect Of Kiwifruit Juice Turmeric Extract or Their Combinasupporting
confidence: 64%
“…8 are highly abused with some abusers taking a combination of both drugs [2,3]. Both substances have been reported to cause damage to hepatocytes [2,15] via oxidative stress [7,9]. The lipid-soluble vitamin, vitamin E is known to protect hepatocytes from damage caused by oxidative stress [13].…”
Section: Comparison Of Percentage Conjugation Of Bilirubin In the Difmentioning
confidence: 99%
“…SC, administered separately and in combination with tramadol has been reported to damage the liver cells [2,7]. Tramadol administration alone has also been reported to damage the liver cells [9,25]. UCB is formed form phagocytosis of haemoglobin (Hb) released from red blood cells that have been destroyed or haemolysed.…”
Section: Comparison Of Percentage Conjugation Of Bilirubin In the Difmentioning
confidence: 99%
See 1 more Smart Citation